Deleuze and Beckett - Wilmer, S.E.; Zukauskaité, Audroné (New York Palgrave Macmillan, 2015)
Deleuze and Beckett is a collection of essays illuminating similarities between the philosophies and practices of Deleuze and Beckett. The contributors include some of the leading Beckett and Deleuze specialists in the world, and their essays address different ideas and concepts of Deleuzian philosophy as well as a wide range of Beckett's oeuvre, including his novels, short stories, stage and television plays, and film work. The book considers Deleuze's interpretation of Beckett's work and demonstrates that Deleuzian concepts and ideas can be usefully applied to Beckett's texts in order provide a greater understanding of Beckett's characters and their journeys. Deleuze's philosophy helps us to recognize that what has been seen as the private territory of despair, loneliness, and emptiness in Beckett's work masks a world of flow and fluctuation that expresses multiple and heterogeneous possibilities.